AN ANALYSIS OF STUDENTS' ERRORS IN ENGLISH DESCRIPTIVE WRITING: A STRUCTURED NARRATIVE REVIEW AND PEDAGOGICAL SYNTHESIS - Dewi Afriany Susanti; Tina Sheba Cornelia Sitompul (Sensei International Journal of Education and Linguistic, 2026)
Descriptive writing looks easy because the students only describe a person or a place, but actually many students still make errors in grammar, vocabulary, and also the organization. This article analyzes students' errors in English descriptive writing. The method used is literature review from journals about error analysis and second language writing. The result shows that the errors are mostly in the tense, the article, the plural, the preposition, the word choice, and also the spelling. Some errors are because of the influence of the first language and some are because the students have not mastered the rule. Therefore the teacher must not only correct the errors but also teach the students how to revise their own writing.